ON THE LIFE SPAN OF INDIVIDUALS (Scientific journal of the Fergana State University, 2023)
The article discusses questions about the life span of individuals. Two out of dozens of theories on the aging mechanism are analyzed in detail: the genetic theory and the theory of natural deterioration of living organisms. The theory of aging and the theory of natural deterioration of structures have their place in science, not because they have good reason for this, but because science has not yet been able to properly refute them.